OPTIMALISASI LAHAN PEKARANGAN KELUARGA MELALUI SINERGI PROGRAM P2B DAN KEMANDIRIAN PANGAN DI KOTA PROBOLINGGO - Siti Munifah; Amalia Juniarti (Ininnawa : Jurnal Pengabdian Masyarakat, 2026)
Efforts to achieve national food self-sufficiency can begin by strengthening food security at the household level through the Nutritious Food Yard (P2B) program. This community service activity aims to optimize residential yards in Probolinggo City through synergy between academia, government, and the community. The method employed is a participatory approach involving a "Rembug Tani" (Farmer Forum) attended by 400 participants, followed by technical mentoring and evaluation of 14 beneficiary groups. Evaluation results show that 35.71% of the groups achieved the "Lestari" (Sustainable) category with aesthetic and productive management. The integration of crop cultivation and poultry farming has proven effective in creating organic fertilizer independence while increasing family income and nutrition. The P2B program effectively supports the Cheap Food Movement based on local resource